Use, knowledge, and effectiveness of nutritional traffic light label in an urban population from Ecuador: a pilot study - Santiago Teran; Isabel Hernandez; Wilma Freire; Beatriz Leon; Enrique Teran (BMC, 2019)
Abstract Background The nutritional traffic light label (NTLL) has become one of the most used Front of Package labels (FOP's) around the world, for its simple and easy to understand graphical system. In Ecuador, this labelling system has recently been implemented; then, this research aims to evaluate the use and knowledge of NTLL and its effectiveness as a public health promotion strategy. Method In a cross-sectional study at two different urban supermarkets in Quito-Ecuador, a survey was conducted in 73 participants to inquire about knowledge, perspectives and purchasing habits regarding the NTLL. Objective data obtained from pictures of the participants'purchase was compared with subjective data obtained from the survey. For categorical variables, Chi square or Fisher's Exact test were used and variables with a statistical significance at α = 0.1 were included in multivariate logistic regression models. Results 88.7% of participants knew about the NTTL. 27.4% reported using the NTLL, while 28.4% of participants were observed to really use it. Significant associations between self-knowledge of the NTLL and education level (p = 0.007) or knowledge level (p = 0.001) were found. A significant association was also found between the refered use of the NTLL and the shopping influencing factor (p = 0.02). In the multivariate analysis an association between knowledge of the NTLL and observed use was found only when adjusted for the supermarket (p = 0.038). Conclusion This study found that the level of knowledge of the NTLL in the studied population was relatively high; however, both the referred and the observed use of the NTLL were low. Use and knowledge of the NTLL were associated with the socioeconomic and educational status of the participants. Thus, the change in nutritional patterns needs additional strategies to put the NTLL before the brand once customers make their purchases.